Faire compter les machines - Cléo Collomb (Communication)
The architext concept is a situated concept. It was formulated some 20 years ago to deconstruct the advertising rhetoric of interactivity and the myth of the “human machine” by looking at the textual mediations that allow texts to be displayed on screens. This article is driven by the desire to include non-humans in research on screen-based writings. It offers an epistemological reformulation of the concept of architext to add a technosemiotic dimension that makes it possible to incorporate the activities of computational machines into the concrete dimension of computerized media.